An immunocompetent patient with a nonsense mutation in NHEJ1 gene - Hossein Esmaeilzadeh; Mohammad Reza Bordbar; Zahra Hojaji; Parham Habibzadeh; Dorna Afshinfar; Mohammad Miryounesi; Majid Fardaei; Mohammad Ali Faghihi (BMC, 2019)
Abstract Background DNA double-strand breaks (DSBs) are among the most deleterious types of DNA damage. DSBs are repaired by homologous recombination or non-homologous end-joining (NHEJ). NHEJ, which is central to the process of V(D)J recombination is the principle pathway for DSB repair in higher eukaryotes. Mutations in NHEJ1 gene have been associated with severe combined immunodeficiency. Case presentation The patient was a 3.5-year-old girl, a product of consanguineous first-degree cousin marriage, who was homozygous for a nonsense mutation in NHEJ1 gene. She had initially presented with failure to thrive, proportional microcephaly as well as autoimmune hemolytic anemia (AIHA), which responded well to treatment with prednisolone. However, the patient was immunocompetent despite having this pathogenic mutation. Conclusions Herein, we report on a patient who was clinically immunocompetent despite having a pathogenic mutation in NHEJ1 gene. Our findings provided evidence for the importance of other end-joining auxiliary pathways that would function in maintaining genetic stability. Clinicians should therefore be aware that pathogenic mutations in NHEJ pathway are not necessarily associated with clinical immunodeficiency.